Bridging Narratology, Ethnology, and Semiotic: A New Naratoethnosemiotic Framework for Reconstructing Banjar Identity in Local Fiction by Jamal T. Suryanata - Kamal Hasuna; Heppy Lismayanti (UIN Raden Mas Said Surakarta, Indonesia, 2026)
Banjar ethnic identity is increasingly subject to erosion as a consequence of modernisation and globalisation; however, it continues to be preserved and articulated within local literary expressions. To address a significant gap in the literature, which has largely examined Banjar literary works through single analytical lenses, this study introduces a novel, integrative